Students’ rhetorical structure mastery of the finding and discussion section in English thesis - Syafryadin, Syafryadin; Harahap, Alamsyah; Astrid, Annisa; Sudarmaji, Imam (JEES (Journal of English Educators Society), 2022)
This study aimed to determine the rhetorical structure of the finding and discussion chapters on the thesis and their problems. This study applied a mixed method. The sample of this research was 30 parts of the finding and discussion of the theses of Bengkulu University English Education postgraduate students who graduated from 2019 to 2020. This study used a checklist as a research instrument. The data obtained were analyzed qualitatively by applying several stages such as data reduction, data presentation and drawing conclusions, while quantitative data were obtained through SPSS. The results indicated that students' mastery of rhetorical structures, especially in the finding and discussion section, is categorized as high and medium, where in the finding section, the average value of students was 41 which is categorized as high, while the average value in the discussion section is 37 which is included in the medium category. The next finding was that some students had difficulty in writing the finding and discussion chapters. These problems included analyzing data, interpreting data, writing discussion sections, incomplete rhetorical structures in writing, mastery of English including vocabulary and grammar, writing the evaluation section in the discussion, coherence and cohesiveness in writing and personal problems. HIGHLIGHTS : Rhetorical structure mastery in Findings of Thesis was categorized as high. Rhetorical structure mastery in Discussion of Thesis was categorized as medium. Several students faced challenges in mastering rhetorical structure of findings and discussion,especially interpretation, rhetorical structure, and discussion of findings.